Value Determinants of Readiness for Volunteer Activities in Individuals - Palkin K.A (Moscow State University of Psychology and Education, 2019)
The article provides a review of published works on psychological components of personality in volunteers. The analysis is accompanied with the outcomes of a study aimed at revealing psychological determinants of volunteering. The study involved a survey of 400 people (including 300 volunteers) based on the "Terminal Values Scale" technique (by I.G. Senin).Statistical data analysis confirmed the hypothesis about the fundamental differences in the structure of human values of volunteers and non-volunteers. Moreover, insignificant gender influences were detected as well as a weak correlation between the length of volunteering experience and certain values that occupied different positions in the value hierarchies of newcomer and experienced volunteers. The paper concludes that research in this field needs to be continued in order to achieve a more detailed picture of the revealed differences and to explore other determinants of volunteering in the structure of the respondents' personality, so that a truly reliable image of the modern volunteer's collective personality would become available.